Role of Emotional Intelligence of Teachers in Emerging Education Scenario: Exploring the Impact of Emotional Intelligence in the Teaching Profession (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In olden days it was believed that a person with high Intelligence Quotient (IQ) could be a successful teacher but now teaching profession has become so challenging that a teacher with high IQ may not be successful unless he or she has emotional intelligence. Initially Emotional Intelligence (EI) was considered as the construct of psychology. Since the change is the law of nature so teaching profession is controlled by several external factors such as class size, number of teachers in institution, working hours, salary and allowances and education policy. The intrinsic factors such as mastery of subject, style of teaching, communication skill and personality of teacher also affect teaching learning process. Emotional Intelligence (EI) has its root in the field of psychology but gradually it moved into the field of education via the human resource development theories. Since the evolution of the term “Social Intelligence”, many researches have been carried out on Emotional Intelligence till date, but in the present research article the author has tried to take out the gist of those similar researches carried out so far on the Emotional Intelligence.